2015
DOI: 10.1371/journal.pone.0134428
|View full text |Cite
|
Sign up to set email alerts
|

Islet Oxygen Consumption Rate (OCR) Dose Predicts Insulin Independence in Clinical Islet Autotransplantation

Abstract: BackgroundReliable in vitro islet quality assessment assays that can be performed routinely, prospectively, and are able to predict clinical transplant outcomes are needed. In this paper we present data on the utility of an assay based on cellular oxygen consumption rate (OCR) in predicting clinical islet autotransplant (IAT) insulin independence (II). IAT is an attractive model for evaluating characterization assays regarding their utility in predicting II due to an absence of confounding factors such as immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 30 publications
4
38
1
Order By: Relevance
“…Despite lower absolute insulin secretion in CC islets, comparable efficiency of reversing diabetes was observed after implantation in NOD-scid mice at comparable doses. The oxygen consumption rate has been shown to be predictive of the islet graft outcome (Papas et al, 2015), with poor oxygenation being a critical factor underlying islet encapsulation failure (Papas et al, 2016;Smith et al, 2017). We found that the in vitro oxygen consumption rate was similar between unencapsulated and encapsulated SC islets, suggesting that overall viability was not compromised by conformal coating.…”
Section: Discussionsupporting
confidence: 55%
“…Despite lower absolute insulin secretion in CC islets, comparable efficiency of reversing diabetes was observed after implantation in NOD-scid mice at comparable doses. The oxygen consumption rate has been shown to be predictive of the islet graft outcome (Papas et al, 2015), with poor oxygenation being a critical factor underlying islet encapsulation failure (Papas et al, 2016;Smith et al, 2017). We found that the in vitro oxygen consumption rate was similar between unencapsulated and encapsulated SC islets, suggesting that overall viability was not compromised by conformal coating.…”
Section: Discussionsupporting
confidence: 55%
“…Combining this with the islet oxygen consumption rate to calculate the total OCR transplanted per kilogram body weight yields an even more reliable benchmark for predicting insulin independence in auto- and alloislet transplantation [45, 6163], and this metric encompasses both the total amount of tissue transplanted and the viability of that tissue. By applying this approach to previously presented data [62, 63], the viability improvements observed with QMS would improve insulin independence rates from 29% to 69% in autograft patients and from 38% to 92% for allograft recipients.…”
Section: Resultsmentioning
confidence: 99%
“…The growth profile is characterized by changes in percent oxygen saturation as this has been correlated to viability [36]. The 10C5M heterospheroid exhibits an early increase in oxygen consumption unlike any of the other cell systems, suggesting that the 10C5M heterospheroid uniquely demonstrates synergistic growth between the two cell types – cancer cell and macrophage, similar to that demonstrated in vivo .…”
Section: Discussionmentioning
confidence: 99%